Firm Level Implications of Early Stage Venture Capital Investment - An Empiri cal Investigation - Dirk Engel; Max Keilbach (Max Planck Institute for Research into Economic Systems, 2005)
The paper analyses the impact of venture capital finance on growth and innovation activities of young German firms. Among other variables, our panel of firm data includes data on venture capital funding and patent applications. With statistical matching procedures we draw an adequate control group of nonventure funded but otherwise comparable firms. The analysis confirms other findings that venture funded firms in Germany have higher number of patent applications than those in the control group. However, they do so already before the venture capitalists engagement. After this engagement, the number of patent applications does not differ significantly from that of the control group, however the venture funded firms display significantly larger growthrates. We conclude that the higher innovation output of venture funded firms is mainly driven by the selection process made by the venture capitalist.
Keywords: C33; C14; D92; D21; L21; 330; Firm Demography; Firm Start-Ups; Firm Growth; Venture Capital; Patented Innovations; Microeconomic Evaluation Methods; Risikokapital; Unternehmensgründung; Innovation; Unternehmenswachstum; Schätzung; Deutschland